The Effect of Educational Videos on Knowledge and Attitudes about Cardio Pulmonary Resuscitation as an Aid for Drowning Victims in Fishermen of Muara Angke - Sandra, Reghula Maryeti; Febriati, Reni; Salma, Zahrotus (Adi Husada Nursing Journal, 2025)
Drowning is a life-threatening emergency due to shortness of breath caused by lungs submerged in fluid. Fishermen are one group of people who must understand first aid treatment for drowning victims. Knowledge of first aid for drowning victims is important because drowning victims require immediate treatment or assistance. The knowledge that can be provided to fishermen is educational videos. This study aimed to explain the effect of educational videos on knowledge and attitudes about CPR as a first aid for drowning victims among fishermen in Muara Angke. In this study, we employed a quasi-experimental design with a one-group pre-post test approach. This study used a sample of 16 respondents. The independent variable of this study is the CPR educational video, and the dependent variable is Knowledge and Attitude in helping drowning victims. The results of the t-test analysis obtained differences in knowledge before and after being given an educational video about CPR, the p value was 0.000 (p value <0.05), while the difference in attitude before and after being given an educational video about CPR, the p value was 0.001 (p value <0.05). This indicates that there is a significant difference between knowledge and attitude in carrying out CPR in respondents before and after being given an educational video about CPR as Basic Life Support for drowning victims. Audiovisual media such as educational videos can be an effective learning method in increasing individual understanding and awareness of first aid measures, especially cardiopulmonary resuscitation.